Development and acceptability testing of a mental health promotion intervention using the Medical Research Council framework. Issue 2 (4th March 2022) - Williams, Emma; Allison, David; Willis, Sarah
ABSTRACT: Young people are at a high risk of developing mental health disorders or illnesses. Mental health promotion (MHP) interventions can reduce this risk. Using the Medical Research Council (MRC) framework for the development and evaluation of complex interventions, this study designed and acceptability tested a methodologically robust school-based mental health promotion intervention. A scoping review and focus groups with stakeholders were conducted during the development phase of the MRC framework. The scoping review involved identifying evidence for effective school-based MHP interventions. Focus groups were then used to determine the acceptability of components identified by the scoping review and to clarify the target or goal of taking part in the intervention. A logic model, showing the theory of change underpinning an intervention designed on the basis of this development phase, was subsequently developed. The scoping review established that MHP interventions typically focus on stigma and stereotypes, mental health literacy and knowledge and help-seeking, and use these foci to determine impact. Common intervention components include group discussion, videos, presentations, storytelling and handouts. Testing of these commonly occurring components targeting knowledge and attitudes towards mental health and stigma and stereotypes suggested all were acceptable to stakeholders. Using the MRC framework to guide the development and test the acceptability of a MHP intervention, this study has produced a complex evidence-based health promotion intervention using interactive activities and videos. Further phases will involve a process evaluation of the intervention fidelity and feasibility testing.